Metabolism and formation of 2-dodecylcyclobutanone in irradiated ground beef - Hijaz, Faraj (Kansas State University, 2010)
A rapid direct solvent extraction method for the extraction of 2-dodecylcyclobutanone (2-DCB) in irradiated beef using acetonirile was developed and evaluated. The 2-DCB in commercially irradiated ground beef patties was extracted with n-hexane by using a Soxhlet apparatus or with acetonitrile via direct solvent extraction. The hexane and the acetonitrile extracts were evaporated to dryness. Then, the fat in the hexane extract was removed with filtration by standing at -20 °C after the addition of a mixture of ethylacetate and acetonitrile. The defatted extract as well as the acetonitrile extract were purified with a 1 g silica cartridge and was injected into a gas chromatography-mass spectrometry (GC-MS). The 2-DCB concentration in irradiated patties was 0.031 ± 0.0026 ppm (n = 5) for the Soxhlet method and 0.031 ± 0.0025 ppm (n = 10) for direct solvent extraction. The effect of low-energy X-rays on the formation of 2-DCB was investigated in frozen ground beef. Beef patties (85/15) were irradiated by low-energy X-rays and gamma rays at 3 targeted doses of 1.5, 3.0, and 5.0 kGy. The 2-DCB was extracted with n-hexane by using a Soxhlet apparatus and analyzed by GC-MS. There was no significant difference in 2-DCB concentration between gamma-ray- and low-energy X-ray-irradiated patties at all targeted doses. The metabolism of 2-DCB was investigated in vitro and in vivo. The incubation mixture from the in vitro study was extracted with n-hexane by using a Soxhlet apparatus and injected into a GC-MS). The hexane extract from the in vitro study and of rat feces was also derivatized with a silylation reagent and injected into a GC-MS. The average percentage of 2-DCB recovered from the test incubations (2-DCB with S9 and NADPH) was 23%, compared with 50% from the controls (2-DCB in buffer). The GC-MS chromatograms of the derivatized samples showed that 2-DCB was metabolized to 2-dodecylcyclobutanol.
Keywords: Food irradiation; X-ray; Gamma ray; 2-dodecylcyclobutanone; 2-DCB; 2-Dodecylcyclobutanol; Agriculture, Food Science and Technology (0359)